Brivaracetam as add-on treatment in patients with post-stroke epilepsy: real-world data from the BRIVAracetam add-on First Italian netwoRk Study (BRIVAFIRST). (April 2022) - Lattanzi, Simona; Canafoglia, Laura; Canevini, Maria Paola; Casciato, Sara; Irelli, Emanuele Cerulli; Chiesa, Valentina; Dainese, Filippo; De Maria, Giovanni; Didato, Giuseppe; Gennaro, Giancarlo Di; Falcicchio, Giovanni; Fanella, Martina; et al.
Highlights: Adjunctive brivaracetam (BRV) improved seizure frequency in patients with post-stroke epilepsy (PSE) The median daily dose of BRV at 12 months was 100 mg Adjunctive BRV was generally well-tolerated in patients with PSE in clinical practice Most adverse events were rated as mild in intensity Brivaracetam can be a suitable add-on therapeutic option for patients with PSE Abstract: Objective: Post-stroke epilepsy (PSE) is one of the most common causes of acquired epilepsy and accounts for about 10-15% of all newly diagnosed epilepsy cases. However, evidence about the clinical profile of antiseizure medications in the PSE setting is currently limited. Brivaracetam (BRV) is a rationally developed compound characterized by high-affinity binding to synaptic vesicle protein 2A. The aim of this study was to assess the 12-month effectiveness and tolerability of adjunctive BRV in patients with PSE treated in a real-world setting. Methods: This was a subgroup analysis of patients with PSE included in the BRIVAracetam add-on First Italian netwoRk Study (BRIVAFIRST). The BRIVAFIRST was a 12-month retrospective, multicentre study including adult patients prescribed adjunctive BRV. Effectiveness outcomes included the rates of seizure response (≥50% reduction in baseline seizure frequency), seizure‐freedom, and treatment discontinuation. Safety and tolerability outcomes included the rate of treatment discontinuation due to adverse events (AEs) and the incidence of AEs. Results: Patients with PSE included in the BRIVAFIRST were 75 and had a median age of 57 (interquartile range, 42-66) years. The median daily doses of BRV at 3, 6, and 12 months from starting treatment were 100 (100-150) mg, 125 (100-200) mg and 100 (100-200) mg, respectively. At 12 months, 32 (42.7%) patients had a reduction in their baseline seizure frequency by at least 50%, and the seizure freedom rates was 26/75 (34.7%). During the 1-year study period, 10 (13.3%) patients discontinued BRV. The reasons of treatment withdrawal were insufficient efficacy in 6 (8.0%) patients and poor tolerability in 4 (5.3%) patients. Adverse events were reported by 13 (20.3%) patients and were rated as mild in 84.6% and moderate in 15.4% of cases. Significance: Adjunctive BRV was efficacious and generally well-tolerated when used in patients with PSE in clinical practice. Adjunctive BRV can be a suitable therapeutic option for patients with PSE.